Estudios sobre la dispersión y longevidad de la mosca del Mediterráneo Ceratitis capitata Wied., marcada en P32 - Katiyar, Kamta P.; Valerio S., Julio (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Longevity and dispersal habits of the Mediterranean fruit fly were studies in nature under heavy host conditions by releasing P32 labelled adults. Tagged flies were recovered up to 26 days after release. The maximum distance travelled by any labelled individual was 1300 meters while 87.5 of the total number of flies recaptured were collected from the traps located at 200 meters distance from the release point.